Maximizing environmental sound recognition and speech intelligibility using time-frequency masking - Johnson, Eric M.; Healy, Eric W. (The Journal of the Acoustical Society of America, 2023)
Environmental sound recognition is an essential part of the human auditory experience that not only provides a sense of connection to one’s surroundings but also forecasts potential nearby safety hazards. Unfortunately, important environmental sounds can be rendered inaudible or otherwise unrecognizable by modern noise-reduction technology, leading to reduced environmental sound recognition. What is needed is a system that simultaneously provides listeners with access to audible, recognizable environmental sounds and intelligible speech. Many modern noise-reduction systems rely on some form of time-frequency masking, such as the ideal ratio mask. Restricting the output range of this mask by limiting the maximum allowable attenuation of any given time-frequency unit results in a mask that preserves environmental sounds to a certain extent while enhancing speech. In an experiment, subjects with hearing impairment and normal hearing listened to mixtures of sound + speech that had been processed by time-frequency masks with various levels of maximum attenuation, resulting in different amounts of environmental sound preservation. In a dual-task paradigm, environmental sound recognition and speech intelligibility were measured, and it was found that both types of listeners simultaneously attain high levels of performance on both tasks when the attenuation of time-frequency units is limited to 23 dB. [Work supported by NIH F32DC019314, NIH R01DC015521, and The OSU Graduate School.]